Neutrophilic Dermatoses in Antineutrophil Cytoplasmic Antibody-Associated Vasculitis: A French Multicenter Study of 17 Cases and Literature Review. Issue 11 (March 2016) - de Boysson, Hubert; Martin Silva, Nicolas; de Moreuil, Claire; Néel, Antoine; de Menthon, Mathilde; Meyer, Olivier; Launay, David; Pagnoux, Christian; Guillevin, Loïc; Puéchal, Xavier; Bienvenu, Boris; Aouba, Achille
Abstract : Abstract: A few reports suggest combination of ANCA-associated vasculitis (AAV) and neutrophilic dermatoses (ND). We aimed to describe the main characteristics of patients presenting with both AAV and ND in a French cohort and through a systematic literature review, and to discuss the possible common pathogenic process involved. We conducted a retrospective study of patients with both conditions. Patients were selected via the French Internal Medicine Society (SNFMI) and the French Vasculitis Study Group (FVSG). A literature review focusing on a combination of both conditions, concentrated only on publications with well-established diagnoses and individual detailed data. Seventeen patients diagnosed with AAV and ND were identified in this cohort. Twelve patients had granulomatosis with polyangiitis (GPA), 4 had microscopic polyangiitis (MPA) and one had eosinophilic GPA (EGPA). Eight patients, all with GPA, displayed pyoderma gangrenosum (PG). Sweet's syndrome was observed in 6 patients (4 with MPA, one with GPA and one with EGPA) and erythema elevatum diutinum in the other three (2 with GPA and 1 with MPA). The literature review identified 33 additional patients with both conditions, including 26 with GPA. Altogether, of the 50 patients (17 from our study and 33 from the literature review), 33 (66%) patients presented with PG associated with GPA in 29 cases (89%). Corticosteroids were the first-line treatment in conjunction with an immunosuppressive agent in most cases. Outcomes were good and a total of 15 patients experienced a relapse. Patients who relapsed were more likely to have ear, nose and throat manifestation than patients who did not [12/15 (80%) relapsing patients vs. 15/35 (43%) non-relapsing patients; p = 0.03)]. In our stud, the most frequent association concerned GPA and PG. ND should be considered and specifically researched within the spectrum of cutaneous manifestations observed in AAV.